EVALUATION OF THE IMPLEMENTATION OF THE POLICY ON RESTRICTING SINGLE-USE PLASTIC WASTE IN BALI PROVINCE FROM A COLLABORATIVE GOVERNANCE PERSPECTIVE - I Gusti Ayu Agung Desi Pratiwi; Desak Made Trisna Juliantari Dewi (Magister Administrasi Publik Program Pascasarjana Universitas Ngurah Rai, 2026)
Plastic waste has become one of the most critical environmental challenges affecting sustainable development in Bali Province as an international tourism destination. The Provincial Government of Bali enacted Governor Regulation Number 97 of 2018 concerning the Restriction of Single-Use Plastic Waste to reduce the consumption of plastic bags, plastic straws, and styrofoam. Although the implementation of this policy has demonstrated significant progress, several challenges remain, including inconsistent compliance among business actors, limited enforcement, and insufficient collaboration among stakeholders. This study aims to evaluate the implementation of Bali's single-use plastic restriction policy using the Collaborative Governance perspective. A qualitative policy research approach was employed through document analysis, observation, and in-depth interviews involving government agencies, business actors, environmental organizations, customary villages, and local communities. Data were analyzed using the Miles, Huberman, and Saldaña interactive model. The findings indicate that policy implementation has been supported by government commitment, community participation, private sector engagement, and the active role of customary villages. However, inter-agency coordination, monitoring mechanisms, and stakeholder collaboration require further improvement. Strengthening a Collaborative Governance model based on local institutions is recommended to enhance sustainable environmental governance in Bali. Keywords: Collaborative Governance, Policy Evaluation, Single-Use Plastic, Policy Implementation, Bali.